Normative data for pharyngeal pressure generation during saliva, bolus, and effortful saliva swallowing across age and gender. (December 2014) - Lamvik, Kristin; Macrae, Phoebe; Doeltgen, Sebastian; Collings, Amy; Huckabee, Maggie-Lee
<x content-type="archive" xml:space="preserve">Abstract</x> Pharyngeal manometry provides information on both temporal and amplitude aspects of pressure generation during swallowing. This report provides normative data for three channel pharyngeal manometry on these parameters of pressure generation, providing the normal range of swallowing pressure against which impaired swallowing pressures can be compared. Participants were equally divided into four groups according to age and sex: young females (n = 20), young males (n = 20), older females (n = 20), and older males (n = 20). A discrete-sensor 3-channel manometric catheter measured pharyngeal pressure during three swallowing conditions: saliva swallowing, 10 ml bolus swallowing, and effortful saliva swallowing. Amplitude of peak pressure (mmHg) was recorded for each sensor during the swallow. The latency (ms) between peak pressure at Sensor 1 (approximately BOT) and Sensor 2 (approximately laryngeal additus) and total duration of upper esophageal sphincter relaxation were recorded. Additionally, a pharyngeal composite measure, consisting of an average of the peak amplitude of the two sensors in the pharyngeal segment, was generated to compensate for potential imprecision in recording due to intra-swallow catheter movement. Statistical analyses included derivation of means and 95% confidence intervals across swallowing conditions and participant groups. Clinically, these data provide a comparative database for identification of pathologic pharyngeal functioning in patients with swallowing impairment, and may aid in future studies of swallowing biomechanics.